ADMINISTRATIVE AND LEGAL REGIME OF THE NORTHERN DELIVERY AS A FACTOR OF SUSTAINABLE DEVELOPMENT OF THE NORTH AND THE ARCTIC ZONE OF RUSSIAN FEDERATION - Galina V. Goncharuk (Russian Studies in Law and Politics)
Achieving “accelerated social and economic development” of the Russian North and the Arctic presupposes, among other things, the uninterrupted supply of hard-to-reach territories, to which there is no year-round access by land transport, with essential goods (food, medicine, fuel). At different periods of time, different delivery schemes were used to supply such territories - with a greater or lesser degree of state participation. Thus, during the Soviet period, northern deliveries were carried out entirely at the expense of the state. All experts note the high level of organization, the absence of failures, the wide range and volume of all necessary goods. With the country's transition to a market economy, the implementation of northern delivery activities was transferred to the level of the constituent entities of the Russian Federation. The decentralized model is characterized by disruptions in the supply of goods, their narrow range, low volume and inflated prices. Since 2024, a new special federal law on northern delivery has come into force, and by-laws are being actively developed and adopted to regulate the processes of delivering goods to hard-to-reach areas of the country. An analysis of the newly adopted regulatory documents indicates a return to centralized state management of northern deliveries. Conducting research on the role of public administration in the process of implementing northern delivery and its impact on the socio-economic development of the North and the Arctic is timely, which represents the relevance of the article. As a result of the study, conclusions were drawn that state regulation of northern imports today is the basis for the socio-economic development of the North and Arctic of Russia.